Quantifying the Visual Experience of Three-dimensional Built Environments. Issue 1 (1st January 2018) - Chang, Dongkuk; Park, Joohee
Abstract : The object of visual experiences in three-dimensional built environments can be considered as a collection of surfaces that are recognized by the human senses. This study suggests a way to interpret mutual visual relationships of surfaces based on the visual amount of light that reflects between surfaces. For this purpose, Three-dimensional Visibility Analysis (TVA) has been created as a platform for understanding the architectural implications of visual experiences in three-dimensional built environments by classifying the visual experiences into seven indices and quantifying them. We first examined the architectural meaning of each visual index through simple models to comprehend how visual relations operate between objects′ surfaces and explored the visual properties of the three-dimensional built environments and their architectural significance in them. Two types of case studies using these visibility indices were undertaken to investigate their objective meanings and to provide potential applications that might be adoptable for practical applications of the built environment, as well as to find associations with how these factors are affected by the social behavior that occurs in it.